AN INVESTIGATION ON DEVELOPMENT OF A FUZZY CONTROLLER FROM THE VIEW OF STATE-SPACE SYSTEM - ALFIAA BASALLOM, SADDAM HASAN (IRC, 2016)
This project aims to develop and design a fuzzy logic controller based on state space modelling. The object of this project to investigate the Fuzzy logic controller and evaluate its viability and laminations as an approach. Moreover, both controllers state-feedback and Fuzzy logic controllers was done in MATLAB/Simulink in order to compare their performance and practicability. Furthermore, the design and modelling of fuzzy logic controller becomes more useful and expected to improve the efficiency and productivity of industrial process such as temperature, pressure and flow. Simulation and implementation results showed that the developed controllers have less overshoot, good control performance, better handling ability, great robustness and are more flexible.